Thermal Analysis of Foods: A Review - Dr. Manju Singh, Dr. Ramesh Dabas (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
Out of a wide variety of techniques of thermal analysis, only few are significant for food analysis.The technique in which a physical property of a substance is measured as function of temperature whereas and the material is under controlled temperature program is called Thermal Analysis. The main thermal techniques for food analysis are- thermal mechanical analysis (TMA), thermogravimetry (TG),dynamic mechanical analysis (DMA), differential scanning calorimetry (DSC) and differential thermal analysis (DTA). Protein, mainpart of large variety of foods and, apart from its nutritional values, contributes to the functional properties of various foods. Protein processing and conformation with DSC study is helpful in explaining protein aggregation, gelatin and denaturation mechanism also gives a path to get maximum utility of proteins.